Metformin suppresses adipogenesis through both AMP-activated protein kinase (AMPK)-dependent and AMPK-independent mechanisms. (15th January 2017) - Chen, Suet Ching; Brooks, Rebecca; Houskeeper, Jessica; Bremner, Shaun K.; Dunlop, Julia; Viollet, Benoit; Logan, Pamela J.; Salt, Ian P.; Ahmed, S. Faisal; Yarwood, Stephen J.
Abstract: People with Type 2 diabetes mellitus (T2DM) have reduced bone mineral density and an increased risk of fractures due to altered mesenchymal stem cell (MSC) differentiation in the bone marrow. This leads to a shift in the balance of differentiation away from bone formation (osteogenesis) in favour of fat cell development (adipogenesis). The commonly used anti-diabetic drug, metformin, activates the osteogenic transcription factor Runt-related transcription factor 2 (Runx2), which may suppress adipogenesis, leading to improved bone health. Here we investigate the involvement of the metabolic enzyme, AMP-activated protein kinase (AMPK), in these protective actions of metformin. The anti-adipogenic actions of metformin were observed in multipotent C3H10T1/2 MSCs, in which metformin exerted reciprocal control over the activities of Runx2 and the adipogenic transcription factor, PPARγ, leading to suppression of adipogenesis. These effects appeared to be independent of AMPK activation but rather through the suppression of the mTOR/p70 S6K signalling pathway. Basal AMPK and mTOR/p70 S6K activity did appear to be required for adipogenesis, as demonstrated by the use of the AMPK inhibitor, compound C. This observation was further supported by using AMPK knockout mouse embryo fibroblasts (MEFs) where adipogenesis, as assessed by reduced lipid accumulation and expression of the adipogeneic transcription factor, C/EBPβ, was found to display an absolute requirement for AMPK. Further activation of AMPK in wild type MEFS, with either metformin or the AMPK-specific activator, A769662, was also associated with suppression of adipogenesis. It appears, therefore, that basal AMPK activity is required for adipogenesis and that metformin can inhibit adipogenesis through AMPK-dependent or -independent mechanisms, depending on the cellular context. Highlights: Metformin can inhibit adipogenesis through AMPK-dependent or -independent mechanisms, depending on the cellular context. Metformin suppresses adipogenesis in C3H10T1/2 mesenchymal stem cells (MSCs), independently of AMPK. Metformin exerts reciprocal control over osteogenic (Runx2) and adipogenic (PPARγ) transcription factors in MSCs. Basal AMPK and mTOR/p70 S6K activity are required for adipogenesis in MSCs.